The costs and benefits of a cigarette ban. Issue 6 (3rd March 2017) - Doucet, Mathieu
Abstract : The death toll from tobacco is staggering: it might contribute to one billion premature deaths over the course of the 21st century. In 'The case for banning cigarettes', Kalle Grill and Kristin Voigt argue that the well-being and equality benefits of a complete ban on cigarettes more than justify the restrictions on autonomy that such a ban would impose. Their argument depends on two crucial simplifications: an assumption that the ban would be effective and the restriction of the analysis to a comparison with the status quo, rather than a broader range of policy options. I argue that despite the authors' claims, these two simplifications make it impossible for their argument to 'bring into focus the fundamental normative issues' surrounding a possible cigarette ban, since they dramatically overstate the benefits and obscure the most significant costs of such a ban.